Hepatoprotective and Antibacterial Activity of Ursolic Acid Extracted from Hedyotis corymbosa L. (Bangladesh Journal of Scientific and Industrial Research, 2010)
Hedyotis corymbosa (L) (Khetpapra in Bengali), a weedy herb of Rubiaceae family is used as a traditional medicine in Bangladesh for the treatment of Jaundice and other liver disorders. In the present study, hepatoprotective and anti-bacterial activity of ethanolic extract of the herb and ursolic acid isolated from it were investigated against paracetamol induced hepatotoxicity in Long Evan's rats and also against some selective gram positive and ten gram negative bacteria. The ethanolic extract of the plant showed significant hepatoprotective effect as evident by decreased serum enzyme levels, SGPT, SGOT, SAKP and SBIL, and also by normal histological architecture of the liver when compared to the paracetamol treated group. Moreover, ethanolic extract, n-hexane fraction and ursolic acid showed maximum activity of 18, 19, 21 mm against Sarcina lutea, Klebsiella pneumonia and Staphylococcus aureus respectively when compared with standard kanamycin disc (30 μgm/disc). These results thus support Hedyotis corymbosa and ursolic acid as hepatoprotective and antibacterial agent. Key Words: Hedyotis corymbosa; Ursolic acid; Hepatoprotective activity; Antibacterial activity. DOI: 10.3329/bjsir.v45i1.5174 Bangladesh J. Sci. Ind. Res. 45(1), 27-34, 2010